Usefulness of intraoperative transcranial sonography in patients with traumatic brain injuries: a comparison with postoperative computed tomography - Mahn Jeong Ha; Seung Han Yu; Jung Hwan Lee; Hyuk Jin Choi; Byung Chul Kim (Journal of Trauma and Injury)
Purpose The aim of this study was to assess the agreement between intraoperative transcranial sonography (TCS) and postoperative computed tomography (CT) in patients with traumatic brain injuries. Methods We performed a retrospective cross-sectional study of 35 patients who underwent TCS during surgery, among those who presented to a regional trauma center and underwent decompressive craniectomy between January 1, 2017 and April 30, 2020. Results The mean difference between TCS and CT in measuring the midline shift was –1.33 mm (95% confidence interval, –2.00 to –0.65; intraclass correlation coefficient [ICC], 0.96; P<0.001). An excellent correlation was found between TCS and CT in assessing contralateral subdural hematomas (ICC, 0.96; P<0.001) and focal hematoma lesions (ICC, 0.99; P<0.001). A very good correlation between TCS and CT was found for measurements of ventricle width (ICC, 0.92; P<0.001). Conclusions TCS during surgery is considered an effective diagnostic tool for the detection of intraoperative parenchymal changes in patients with traumatic brain injuries.